S44 Increased expression of immunoreactive thymic stromal lymphopoetin in severe asthma. (16th November 2010) - Shikotra, A; Hargadon, B; Shelley, M; Bennett, J; Brightling, C; Austin, C; Choy, D F; Wu, L C; Arron, J R; Bradding, P
Abstract : Background: Thymic stromal lymphopoetin (TSLP) is a cytokine implicated in the pathophysiology of asthma through two pathways: a TSLP-OX40L-T cell axis and a TSLP-mast cell axis. Whether these pathways operate in human asthma is unknown. Aims: To investigate whether mucosal TSLP protein expression relates to asthma severity, and distinct immunological pathways. Methods: GMA-embedded bronchial biopsies from healthy subjects (n=12) and patients with mild (BTS step 1, n=8), moderate (BTS steps 2 and 3, n=12) and severe (BTS steps 4 and 5, n=16) asthma were immunostained for TSLP, OX40, OX40L, CD83, IL-13, and inflammatory cell markers. Extent of immunostaining was correlated with clinical data. Results: Specific TSLP immunoreactivity was evident in both the airway epithelium and lamina propria of both healthy and asthmatic subjects. TSLP immunoreactivity was not present in airway smooth muscle. TSLP epithelial expression was significantly elevated in asthma as a whole compared to healthy controls (p=0.0005), particularly in mild and severe disease. The number of TSLP+ cells in the lamina propria was elevated in patients with severe asthma relative to other groups (p=0.0058). Co-localisation studies in 6 severe asthmatic subjects showed that 5% of TSLP+ cells in the lamina propria were CD68+ macrophages and 20% were tryptase+ mast cells. There were significant inverse correlations between TSLP counts in both the asthmatic bronchial lamina propria and epithelium with the FEV1 /FVC ratio (rs =−0.53, p=0.002 and rs =−0.40, p=0.037). Immunostaining for OX40, OX40L and CD83 in the airways was sparse, with no difference between asthmatic patients and normal control subjects. IL-13 staining was increased in non-epithelial cells within the airway epithelium in severe asthma (p=0.033). Conclusions: TSLP expression is elevated in severe asthma despite high dose corticosteroid therapy. Although we did not detect activity of the TSLP-OX40L-T cell pathway within asthmatic bronchial mucosa, it is possible that this pathway operates in secondary lymphoid organs such as draining lymph nodes. The close approximation of airway stroma and mast cells suggests that the TSLP-mast cell axis, in which TSLP and IL-13 operate in a positive regulatory loop, is active in asthmatic bronchial mucosa and may be important in maintaining chronic airway inflammation.